Clinical value of the Integrated Pulmonary Index® during sedation for interventional upper GI-endoscopy: A randomized, prospective tri-center study. Issue 1 (January 2017) - Riphaus, Andrea; Wehrmann, Till; Kronshage, Tim; Geist, Christoph; Pox, Christian P.; Heringlake, Stefan; Schmiegel, Wolff; Beitz, Analena; Meining, Alexander; Müller, Michaela; von Delius, Stefan
Abstract: Background and study aims: The Integrated Pulmonary Index ® (IPI) is a mathematically-determined factor based on parameters of capnography and pulse oximetry, which should enable sensitive detection of impaired respiratory function. Aim was to investigate whether an additional measurement of the IPI during sedation for interventional endoscopy, compared to standard monitoring alone, allows a reduction of sedation-related respiratory depression. Patients and methods: 170 patients with standard monitoring randomly underwent either a blinded recording of capnography (control group, n = 87) or capnography, including automated IPI calculation (IPI group, n = 83), during deep sedation with midazolam and propofol. The primary endpoint was the maximum decrease of oxygen saturation from the baseline level before sedation. Secondary endpoints: incidence of hypoxemia (SaO2  < 90%), other sedation-related complications (apnea rate, bradycardia, hypotension), patient cooperation and satisfaction (VAS). Results: Mean propofol dose in the IPI group (245 ± 61 mg) was comparable to the control group (225 ± 47 mg). The average drop of the oxygen saturation in the IPI group (6.5 ± 4.1%) was nearly identical to that of the control group (7.1 ± 4.6%, p = 0.44). Apnea episodes >15 s was found in 46 patients of the control and 31 of the IPI group (p < 0.05). Frequency of occurrence of a drop in pO2 -saturation <90%, bradycardia <50/min or a drop of systolic pressure <90 mmHg were not significantly different in both groups. Mechanical ventilation was not required in any case. Patient cooperation and satisfaction were assessed similar in both groups. Conclusion: A clinically appealing advantage of IPI-assessment during deep sedation with midazolam and propofol for interventional endoscopy could not be documented. However, IPI registration was more effective in reducing the incidence of apnea episodes.